The impact of the Ukraine war on the relations between Iran and Russia - ELAHEH KOOLAEE; Somayye Zangegeh (رهیافتهای سیاسی و بین المللی)
Russia's attack has military consequences not only for Europe and the world but also for the exit door. The political-security relations between Iran and Russia have also been affected by this war. Iran is important against war in two ways. First, Iran's direction in this war affects the relations between the two countries. Second, this issue affects Iran's position in the international system. The main question of this article is "How has Iran's behavior been regarding the war and what effect has it had on its relations with Russia?" The authors assume that "Iran has been cautious about the dangerous war, that is, on the one hand, it has not condemned Russia's involvement in the government, but it has also not supported it." This policy is followed to maintain the relations between the two countries. The people who in this article, the theoretical commentator of neoclassical realism, examine the Islamic Republic of Iran against the war and its impact on Iran's relations with Russia. This research shows that Tehran has found war as a factor in improving and developing relations with Moscow. However, the nature of these relationships does not change fundamentally. From Iran's point of view, the drivers and pillars of relations with Russia are stable. Russia's relations are one of Iran's most important geopolitical partners and it has followed one of its strategies. The method of this research is qualitative with descriptive-analytical.